An Fuzzy Trust Based Energy Aware Multipath Secure Data Collection in WSN - Chitti Babu, Y; Anuradha, Ch; Sri Rama Chandra Murty, P (International Journal of Engineering and Technology, 2018)
A Wireless Sensor Network (WSN) is an array of radar nodules that energetically organize itself into a cable-less grid without utilizing any prevailing arrangement. One of the significant issues in WSNs is the drive’s intake, whereby the grid’s lifespan is reliant on this aspect. Security is another significant issues in cable-less radar grids, because of absence of wire/cable besides resource constraint’s nature. Reliance model shows a key role in fortifying the radar grids by recognizing the egotistical, malevolent and give-in nodules and separating them from message grid. Directed Random Propagation (DRP) operates two-hop vicinity data to enhance the circulation competence, leading to a reduced pack capture possibility. In this study, Shuffled Frog Leaping Algorithm (SFLA) is applied to augment ill-defined faith centered drive conscious multiple route locked data group in WSN.